(untitled) (Rudarsko-geološko-naftni zbornik, 2016)
Human health, the environment, and climate are being profoundly aff ected by complex pollutant interactions in the atmosphere. Almost all human activities cause the emissions of air pollutants. Their understanding and quantifi cation is the fi rst step towards the control and mitigation of air pollution. The general aim of this paper is to summarise the fi ndings of selected Croatian and Indian papers addressing air pollution, particularly those focusing on sulphur and aerosols associated with coal-fi red power plants. The two countries are essentially diff erent regarding their size, geography, history, economy, industrial potential, to name but a few. However, they both have had certain relations to the fossil fuel extraction and its usage in power stations and industry for decades. Various research approaches are presented, together with a brief outline of national air pollution policies.